Interprofessional Conflicts in Health: Major barrier to Quality Health Care Practice - Muhammad Umar, Misbah Marryam (Pakistan Journal of Medical & Health Sciences, 2022)
Interprofessional term has a wide perspective and it includes all professionals from different specialized health departments like nursing, occupational therapy, physical therapy, speech and language pathology, social work, and other health professionals besides the physicians with different specialties1. When different professionals work in collaboration for providing quality care to the patient, it is the patient who is benefited the most; a major goal of all the health care professionals2. But unfortunately whenever health professionals work together as a team, conflict occurs. There are sometimes unnecessary arguments between different professionals for taking the lead. But this conflict can lead to serious consequences as it not only affects patient care but also affects one’s own satisfaction with his job, his wellness and professional productivity that also becomes questionable. For a long time all over the world, there was a division of all health professions with in two categories i.e. physicians and other health care professionals. This made all other health professionals as subordinates with most of the patient care dependent just only on physician not only burdening them with extra work but also affecting the practice of other health professions3. However the major reason for conflict is not taking lead but rather it is lack of proper communication. Some other reasons for conflict are lack of knowledge about others roles and responsibilities and about one’s own role, differences in goals, personal and professional values, inequality regarding workload and pay packages .Conflict can occur at individual, professional and organizational level. There are different boundaries of every profession that must be respected to maintain a good working environment as boundary crossing causes conflict4. Being human and as a social animal people are different in all aspects. Some people do not like working with others for multiple reasons but personal and interprofessional respect should be maintained at any cost for patients benefit5.